Prevalence and profile of congenital heart disease and pulmonary hypertension in Down syndrome in a pediatric cardiology service - Felipe Alves Mourato; Lúcia Roberta R. Villachan; Sandra da Silva Mattos (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE:To determine the frequence and profile of congenital heart defects in Down syndrome patients referred to a pediatric cardiologic center, considering the age of referral, gender, type of heart disease diagnosed by transthoracic echocardiography and its association with pulmonary hypertension at the initial diagnosis.METHODS:Cross-sectional study with retrospective data collection of 138 patients with Down syndrome from a total of 17,873 records. Descriptive analysis of the data was performed, using Epi-Info version 7.RESULTS: Among the 138 patients with Down syndrome, females prevailed (56.1%) and 112 (81.2%) were diagnosed with congenital heart disease. The most common lesion was ostium secundum atrial septal defect, present in 51.8%, followed by atrioventricular septal defect, in 46.4%. Ventricular septal defects were present in 27.7%, while tetralogy of Fallot represented 6.3% of the cases. Other cardiac malformations corresponded to 12.5%. Pulmonary hypertension was associated with 37.5% of the heart diseases. Only 35.5% of the patients were referred before six months of age.CONCLUSIONS: The low percentage of referral until six months of age highlights the need for a better tracking of patients with Down syndrome in the context of congenital heart disease, due to the high frequency and progression of pulmonary hypertension.